The Americanization of Peter Carey: A Study of Transnational Influences and Cultural Resistance in Australian Literature - Syofyan, Donny (Universitas Muara Bungo, 2024)
Peter Carey, a celebrated Australian author and two-time Booker Prize winner, is renowned for his global perspective in his literary works. This paper investigates Carey's engagement with American culture and values, employing formal narrative analysis to examine his global mindset as reflected in his fiction. A review of several of his novels suggests that his incorporation of global themes sometimes overshadows his Australian identity. Specifically, the analysis reveals a distinct American influence in Carey's works, evident in the use of black humor, metafiction, and fabulation. This study contributes to a deeper understanding of Carey's literary identity and the complex interplay between national and global influences in his writing.